The Concept of Implementing Merdeka Belajar in Strengthening the Pancasila Student Profile through Pancasila Education Learning in Shaping Students’ Character - M. Taufiqurrahman; Mohamad Abduh; Sri Rumiati (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
This study aims to describe the concept of implementing Merdeka Belajar in strengthening the Pancasila Student Profile through Pancasila Education learning in shaping students’ character at SMA Rimba Madya, Bogor City. The background of this research is based on the importance of character education as an effort to develop students who are faithful and devoted to God Almighty, possess global diversity awareness, are independent, think critically, are creative, and demonstrate mutual cooperation in accordance with Pancasila values. The research method employed is a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects included the principal, Pancasila Education teachers, and students. The results indicate that the implementation of Merdeka Belajar in Pancasila Education learning at SMA Rimba Madya, Bogor City, is carried out through student-centered learning, the provision of freedom of expression and opinion, contextual learning, and the strengthening of projects based on the Pancasila Student Profile. This implementation has been proven to foster character values such as responsibility, tolerance, discipline, cooperation, and a sense of nationalism among students. Thus, the concept of Merdeka Belajar plays a strategic role in strengthening the Pancasila Student Profile through Pancasila Education learning in shaping students’ character.